THE SUCCESSFUL TRANSPLANTATION OF ACROPORA MICROPHTHALMA AT BARRANG LOMPO REEF EDGE< SOUTH SULAWESI - Yuliantri, A. R.; Moka, W.; Jompa, J.; Litaay, M. (Marine Research in Indonesia, 2006)
Research on transplantation of Acropora microphthalma was conducted at Barrang Lompo Island reef edge of South Sulawesi from September to December 2002. The aim of this research was to know the successful rate of several coral transplantation methods for rehabilitation of coral reefs, covering the survival and growth rates. The methods used were framework earthenware (FE), iron stake (IS), dead coral tying (DCT), where the mother colony (MC) was used as control. These transplantation techniques were applied at five meter depth in two stations, north and south sites of the island. The survival rate for each method FE, IS, DCT and MC at the northern station was 85.71; 42.86; 85.71; 57.14%, while for southern station was 85.71; 85.71; 71.43 and 85.71%, respectively. The growth rates observed for each method at the first station were 2.18; 2.02; 1.40; 1.05 cm, and for the second station were 2.56; 2.21; 1.61; 1.04 cm, respectively.